Risk management and financial institutions / John C. Hull - Hull, John
Risk Management and Financial Institutions, Fifth Edition explains all aspects of financial risk and financial institution regulation, helping you better understand the financial markets—and their potential dangers. Inside, you’ll learn the different types of risk, how and where they appear in different types of institutions, and how the regulatory structure of each institution affects risk management practices. Comprehensive ancillary materials include software, practice questions, and all necessary teaching supplements, facilitating more complete understanding and providing an ultimate learning resource. All financial professionals need to understand and quantify the risks associated with their decisions. This book provides a complete guide to risk management with the most up to date information.